2021
DOI: 10.3389/ffgc.2021.727042
|View full text |Cite
|
Sign up to set email alerts
|

Litter Flammability of 50 Southeastern North American Tree Species: Evidence for Mesophication Gradients Across Multiple Ecosystems

Abstract: Widespread fire exclusion and land-use activities across many southeastern United States forested ecosystems have resulted in altered species composition and structure. These changes in composition and structure have been implicated in positive fire-vegetation feedbacks termed “mesophication” where fire spread and intensity are diminished. In forests and woodlands, inherent flammability of different species is the mechanistic driver of mesophication. To date, there has been limited work on documenting the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 45 publications
2
12
0
Order By: Relevance
“…A. rubrum is commonly implicated as a strong mesophyte throughout eastern North America (Nowacki and Abrams 2008;Kreye et al 2013;Kane et al 2021;McDaniel et al 2021). Similarly, a prior study examining flammability in southeastern US species has identified Nyssa sylvatica as being a strong mesophyte (Varner et al 2021). The inclusion of Betula alleghaniensis as a strong mesophyte confirmed our expectations, but our study is the first to report this finding.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…A. rubrum is commonly implicated as a strong mesophyte throughout eastern North America (Nowacki and Abrams 2008;Kreye et al 2013;Kane et al 2021;McDaniel et al 2021). Similarly, a prior study examining flammability in southeastern US species has identified Nyssa sylvatica as being a strong mesophyte (Varner et al 2021). The inclusion of Betula alleghaniensis as a strong mesophyte confirmed our expectations, but our study is the first to report this finding.…”
Section: Discussionsupporting
confidence: 88%
“…There remains a debate over the flammability and ecological roles of Carya spp. in eastern North American woodlands and forests (Pile-Knapp et al 2021;Varner et al 2021). Our data suggest that they function more as a mesophyte, but the clear dichotomy between these two coarse categories is likely more nuanced for this genus and other species (Keeley and Zedler 1998;Varner et al 2021).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Fuel beds are also an important component of sustaining oak ecosystems with fire. Oak leaf litter decomposes slowly, providing a continuous fuel bed with a low bulk density that burns readily when sufficiently dry (Dickinson et al, 2016; Kreye et al, 2013; Nowacki & Abrams, 2008; Varner et al, 2021). Fire exclusion decreases flammability, because litter from mesophytic species decomposes more rapidly and has chemical properties that make their litter less likely to support combustion (Dickinson et al, 2016; Kreye et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…non‐flammable, fast‐flammable, and hot‐flammable species; Pausas et al., 2017). Similarly, plant flammability measurements allow understanding the fire‐vegetation feedbacks that underlie mesophication processes or fire‐driven biological invasions (Murray et al., 2013; Varner et al., 2021). In addition, laboratory tests permit a better control of the conditions during ignition (e.g.…”
Section: Introductionmentioning
confidence: 99%